Faktor–faktor Ekonomi yang Mempengaruhi Kredit Macet dan Pengaruhnya terhadap Cadangan Kerugian Penurunan Nilai (CKPN) di Bank BTN KC Tasikmalaya - Nababan, Darmayanti; Sutarsa, Monika (MASALIQ, 2025)
The purpose of this study is to analyze the economic factors that influence bad loans at Bank BTN KC Tasikmalaya and their impact on the formation of (CKPN). The research method used is qualitative with a descriptive approach. The source of the research is through observation and interviews with banks and debtors. The results of the study show that the economic factors that cause bad loans at Bank BTN KC Tasikmalaya range from very influential to not very influential. These factors include consumptive lifestyle patterns, online lending, online gambling, and the Covid-19 pandemic. This is due to unexpected changes in income or expenses, other loans or online loans, Covid-19 and online gambling, the ease of the application process, then finally shopping habits or consumptive lifestyles. Many customers are stuck in debt with high interest rates through other loans, causing difficulties in meeting credit installment payments. Meanwhile, the Covid-19 that has lasted for the past few years has worsened economic conditions, decreased income, and layoffs, increasing the number of bad loans. The impact of this increase in non-performing loans requires banks to increase the formation of CKPN to anticipate the potential for greater losses. This study suggests that Bank BTN KC Tasikmalaya take a better approach in managing credit risk, taking into account economic factors that affect customer behavior. In addition, banks can strengthen financial education for customers to prevent bad loans caused by consumptive lifestyle factors and online lending.